Drifts, currents, and power scrape-off width in SOLPS-ITER modeling of DIII-D. (August 2017) - Meier, E.T.; Goldston, R.J.; Kaveeva, E.G.; Makowski, M.A.; Mordijck, S.; Rozhansky, V.A.; Senichenkov, I.Yu.; Voskoboynikov, S.P.
Highlights: SOLPS-ITER modeling with drifts produces a realistic power scrape-off width. Magnetic drifts support a realistic scrape-off layer density width. The temperature width is appropriately bounded by the density width. The power width does not vary as expected with poloidal magnetic field. The research paves the way for new discoveries in fusion power exhaust physics. Abstract: The effects of drifts and associated flows and currents on the width of the parallel heat flux channel ( λq ) in the tokamak scrape-off layer (SOL) are analyzed using the SOLPS-ITER 2D fluid transport code. Motivation is supplied by Goldston's heuristic drift (HD) model for λq, which yields the same approximately inverse poloidal magnetic field dependence seen in multi-machine regression. The analysis, focusing on a DIII-D H-mode discharge, reveals HD-like features, including comparable density and temperature fall-off lengths in the SOL, and up-down ion pressure asymmetry that allows net cross-separatrix ion magnetic drift flux to exceed net anomalous ion flux. In experimentally relevant high-recycling cases, scans of both toroidal and poloidal magnetic field ( Btor and Bpol ) are conducted, showing minimal λq dependence on either component of the field. Insensitivity to Btor is expected, and suggests that SOLPS-ITER is effectively capturing some aspects of HD physics. Absence of λq dependence on Bpol, however, is inconsistent with both the HD model and experimental results. The inconsistency is attributed to strong variation in the parallel Mach number, which violates one of the premises of the HD model.